Analysis of Oxyluciferin Photoluminescence Pathways in Aqueous Solutions. (17th November 2014) - Hiyama, Miyabi; Mochizuki, Toshimitsu; Akiyama, Hidefumi; Koga, Nobuaki
Abstract We evaluated the pKa values of oxyluciferin and its conjugate acids and bases theoretically with the help of experimental correction values, from which free energies for the first excited and the ground states of all the species were estimated. On the basis of these results, we calculated pH‐dependent absorption spectra, where the relative absorption intensities of various species strongly depend on photoexcitation energy, and we further analyzed the photoluminescence pathways of oxyluciferin in aqueous solutions with various pH. In the case of 350 nm photoexcitation, in particular, experiments have shown that dominant emission color is green and it attenuates with pH decreasing, while blue (3 < pH < 8) and red (pH < 3) emissions appear. Our present results clarify the pathways of these photoluminescence depending on the pH values and thus should be useful in further analyses of photoluminescence pathways for other photoexcitation wavelength in comparison with experiments.